Balancing on the edge: implications of a UK national audit of the use of BSR-BHPR guidelines for the diagnosis and management of polymyalgia rheumatica. Issue 1 (28th July 2015) - Das, Parthajit; Samanta, Ash; Dasgupta, Bhaskar
Abstract : Introduction: The British Society for Rheumatology and British Health Professionals in Rheumatology (BSR-BHPR) guidelines for management of polymyalgia rheumatica (PMR) were published in 2010, aiming to provide guidance for diagnosis, management and disease monitoring. A national study was conducted across multiple rheumatology units throughout the UK in order to study the level of adoption of guidelines in clinical practice. Methods: This study was a retrospective analysis of patient records with a diagnosis of PMR from multiple centres across the UK. The primary objective was to explore the national compliance of PMR management according to BSR guidelines. Results: We included 81 responses across 10 rheumatology units in the UK. The guideline core inclusion criteria were followed in more than 90% in making the diagnosis of PMR, but limited concordance was observed with respect to excluding PMR-mimics, the initial recommended glucocorticoid dosage (74%), steroid taper (41%), treatment of relapse (76%), bone protection (84%) and patient follow-up (43%). Conclusions: We observed a wide variation in clinical practice and limited adherence to BSR-BHPR guidelines in the UK. This study highlights the need for robust multilayered and multifaceted implementation strategies involving the providers and the consumers for apposite dissemination of guideline-based practice and consistency of care. We believe that the findings of this study have significant relevance for formulation and dissemination of PMR guidelines in the future.